METODOLOGI ANALISIS TEKS BERWAWASAN GENDER: Perspektif Hermeneutik - Iwanebel, Fejrian Yazdajird (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2014)
AbstractProblems of women when seen through the eyes of faith will continue to looksexy. Because religion is often considered "bridging" role of women as both have the mission of humanity and divinity like a man, but it makes the subordinate position of women and marginalized. In response to the discourse on gender, this article tries to make the methodology mewacanakan idea as the basis of modern thinkers, namely Amina Wadud and Khaled Abou El-Fadl. Amina Wadud hermeneutics tauhidi introduced that can be used at the same paradigms and methodologies. While Abou El-Fadl introduce dialogical hermeneutical methodology to bridge the gap in the elements of subjectivity that often occur in the interpretation of gender.Keyword: Amina Wadud, Khaled Abou El-Fadl, hermeneutik